Monocrotophos: Toxicity Evaluation and Respiratory Responses of Cyprinus carpio (Linnaeus) - M. David2, R.A. Maniyar1, R. Nazeer Ahmed1* (Recent Research in Science and Technology, 2010)
Static rencval bioassay method was used to determine the 96 hr LC50 of monocrotophos on Cyprinus carpio. Oxygen consumption and behavioral responses were recorded at lethal and at two sublethal (1/10th and 1/15th) concentrations. Oxygen consumption responses were concentration dependent. The data indicated maximum decrease in oxygen consumption at lethal exposure (86.4 µg/L) over control on 4th day followed by 2nd, 3rd, 1st days. At 1/10th of lethal concentration (8.64 µg/ L) continuous decrease on 1st, 10th and 20th day but decrease was reduced on 30th day. Similar variations were observed at 1/15th of lethal exposure (5.76 µg/ L) from day 1 to day 10. The decrease continued on 30th day which was witnessed to be very less amongst all. Behavioral responses were significant in lethal exposures due to intoxication. Fish showed hyper excitation, erratic swimming, jumping, and lethargy due to low breathing frequency followed by muscular rigidity and abundant mucous secretion over the gills.